Actinobacillus actinomycetemcomitans count in patients with adult periodontitis - MH. Salari; F. Haghighati; F. Dadkhah (Tehran University of Medical Sciences, 1998)
Periodontal infections are categorized into various groups based on patient's age or bacteria presented in dental pockets. There are Juvenile periodontitis, rapidly progressing periodontitis and adult periodontitis. Adult periodontitis is known as the most prevalent cause of tooth loss in adult patients. In current study, 100 teeth of patients who suffered from adult periodontistis were selected, cultured in kapnophil media and analyzed for containing Actinobacillus actinomycetemcomitans bacteria. 34 teeth of 17 patients contained this bacteria. Further discussions are mentioned in the article about sex,age and location of infection in these patients in association to the bacteria presence.